Method for improving diffusion coefficient of perovskite thin film and intercepting high diffusion coefficient of perovskite thin film under high pressure to normal pressure

By applying pressure in a high-pressure press and maintaining it for a long time, the carrier diffusion coefficient of the perovskite film is significantly improved, and the high diffusion coefficient under high pressure is successfully retained to normal pressure, solving the performance of the perovskite film Stability issues under pressure changes.

CN119486553AActive Publication Date: 2025-02-18DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310998520.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-09
Publication Date
2025-02-18
Estimated Expiration
2043-08-09

AI Technical Summary

Technical Problem

The prior art is difficult to significantly increase the carrier diffusion coefficient of perovskite films through simple and efficient physical methods, and maintain the high diffusion coefficient at high pressure to normal pressure.

Method used

By transferring (FAPbI3) 0.95 (MAPbBr3) 0.05 polycrystalline film to the diamond-paired anvil of the high pressure press, applying different pressures and maintaining them for a long time, recording and calculating the diffusion coefficient under different pressures, the high pressure at high pressure was successfully The diffusion coefficient remains until normal pressure.

Benefits of technology

The diffusion coefficient of perovskite film was significantly improved, and the high diffusion coefficient under high pressure was successfully maintained to normal pressure, solving the stability problem of perovskite film performance under pressure changes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004385539740000041
    Figure BDA0004385539740000041
  • Figure BDA0004385539740000042
    Figure BDA0004385539740000042
  • Figure BDA0004385539740000043
    Figure BDA0004385539740000043
Patent Text Reader

Abstract

The invention discloses a method for improving the diffusion coefficient of a perovskite thin film and intercepting the high diffusion coefficient of the perovskite thin film to normal pressure under high pressure, which comprises the following steps of: crushing a (FAPbI3) 0.95 (MAPbBr3) 0.05 polycrystalline thin film, picking a proper sample by using a needle, and putting the proper sample into a diamond anvil cell; diffusion coefficient changes of the polycrystalline film under different pressures are carried out through a space-time resolution fluorescence imaging system, the pressure is increased from normal pressure to 1.8 GPa, the pressure is released after the pressure is maintained for 12 h, and the diffusion coefficient changes of the polycrystalline film at different moments after pressurization are recorded. According to the invention, the diffusion coefficient test of the polycrystalline film under different pressures is realized. As the pressure increases, the diffusion coefficient of the polycrystalline film increases first and then tends to be unchanged. The diffusion coefficient of the high polycrystalline film under the high pressure is successfully kept to the normal pressure after the pressure is relieved after the pressure is maintained for a long time at the high pressure point.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of material carrier transport, and in particular relates to a method for improving the diffusion coefficient of a perovskite film and intercepting the high diffusion coefficient under high pressure to normal pressure. Background Art

[0002] Organic-inorganic hybrid perovskites have the advantages of high absorption coefficient, long carrier lifetime and carrier diffusion length, and suitable band gap, and have become star materials in the photovoltaic and optoelectronic fields in the past decade. Organic-inorganic hybrid perovskites have attracted extensive and systematic research by scientists around the world. Perovskite materials can be applied to light-emitting diodes, lasers, photodetectors, photocatalysis, and solar cells. The photoelectric conversion efficiency of perovskite solar cells has increased from 3.8% in 2009 to 26% today. Obtaining hybrid perovskites by cation and anion doping is considered an important method to obtain high-efficiency perovskite solar cells. However, the photoelectric conversion efficiency of perovskite solar cells is still far from the Shockley–Queisser limit (33.7%).

[0003] In order to achieve high conversion efficiency of perovskite solar cells, people have been committed to developing various chemical methods to improve the photoelectric properties of perovskites (such as carrier lifetime and carrier transport performance). Various chemical methods include optimizing crystal growth, chemical element doping, and preparing heterojunctions, with the aim of improving the crystallinity of perovskites and optimizing the chemical composition. In addition, different chemical treatment methods, such as solvent engineering and vacuum evaporation, have also been used to improve the performance of perovskites. Chemical regulation will change the composition of elements and is difficult to control precisely. How to use simple and efficient physical methods to improve the performance of perovskites is one of the scientific challenges facing this field.

[0004] As an independent thermodynamic parameter, pressure can effectively shorten the distance between atoms and enhance the coupling of adjacent electron orbits. It has a profound impact on the structure and performance of materials and plays an important role in discovering new phenomena, new properties and explaining new mechanisms. Pressure adjusts the crystal structure and wave function of the material by changing the bond length and bond angle of the lattice, thereby changing the photophysical properties of the material. Carrier lifetime and carrier migration distance are important photophysical parameters that determine the performance of optoelectronic devices. Understanding the changes of these parameters with pressure is crucial to evaluating the impact of pressure-treated perovskites and their devices. Summary of the invention

[0005] For practical application considerations, the application of devices under high pressure environments is still difficult to put into practice. Therefore, the primary task of the present invention is to increase the diffusion coefficient of carriers in the perovskite film by applying pressure, and then maintain the high diffusion coefficient of the perovskite film under high pressure to normal pressure by maintaining the high pressure point for a long time.

[0006] The main implementation scheme of the present invention is as follows: (FAPbI3) 0.95 (MAPbBr3) 0.05 The polycrystalline film was transferred to the diamond anvil of the high-pressure press by needle picking. Stainless steel was used as an annular gasket and placed on the diamond anvil. Silicone oil was dripped into the gasket. The silicone oil was used as a pressure transmission medium to subject the sample to quasi-hydrostatic pressure. The high-pressure press with the sample was placed on a fluorescence scanning imaging microscope system to test the diffusion coefficient under different pressures. The experiment found that as the pressure increased, (FAPbI3) 0.95 (MAPbBr3) 0.05 The diffusion coefficient of the polycrystalline film increases first and then tends to remain constant as the pressure increases. By maintaining the high pressure point for a long time and then releasing the pressure, the high pressure phase (FAPbI3) was successfully 0.95 (MAPbBr3) 0.05 The diffusion coefficient of polycrystalline thin films is preserved to ambient pressure.

[0007] The purpose of the present invention is achieved through the following solutions.

[0008] The method of increasing the diffusion coefficient of the perovskite film and intercepting its high diffusion coefficient under high pressure to normal pressure, the specific steps are as follows: (1)(FAPbI3) 0.95 (MAPbBr3) 0.05 Preparation of polycrystalline thin film: Dissolve the raw materials MABr, MACl, FAI, PbBr2 and PbI2 in a mixed solution of DMF and DMSO, and stir for a certain time until dissolved. Add the precursor solution dropwise onto a thin glass sheet with the size of 22mm×22mm×0.13mm (length×width×thickness), then spin-coat, add trichlorotoluene dropwise during the spin-coating process, and finally perform a heat treatment process. (2)(FAPbI3) 0.95 (MAPbBr3) 0.05 Transferring the polycrystalline film to the diamond anvil: The synthesized sample (1) is selected under a microscope using an embroidery needle and transferred to the diamond anvil of the high-pressure press. Stainless steel is placed on the diamond anvil as a gasket, and silicone oil is dripped into the gasket. The silicone oil serves as a pressure transmission medium to subject the sample to quasi-hydrostatic pressure. (3) (FAPbI3) under different pressures 0.95 (MAPbBr3) 0.05 Diffusion coefficient test of polycrystalline thin film: The sample (2) mounted on the high-pressure press is placed on a fluorescence scanning imaging microscope system built in the laboratory to perform diffusion coefficient tests under different pressures. (4) Intercepted perovskite (FAPbI3) 0.95(MAPbBr3) 0.05 High diffusion coefficient of polycrystalline thin film under high pressure to normal pressure: The sample (2) installed on the high-pressure press was placed on a fluorescence scanning imaging microscope system built by the laboratory. After maintaining the high pressure point for a long time, the pressure was released and the (FAPbI3) at different times was recorded since the start of the pressurization. 0.95 (MAPbBr3) 0.05 Diffusion coefficient variation in polycrystalline thin films.

[0009] Preferably, the synthetic raw materials in step (1) are 5-10 mg methyl ammonium bromide (MABr), 25-30 mg methyl ammonium chloride (MACl), 210-230 mg formamidine hydroiodide (FAI), 20-30 mg lead bromide (PbBr2) and 600-620 mg lead iodide (PbI2), 700-900 μl dimethylformamide (DMF) and 100-300 μl dimethyl sulfoxide (DMSO), and the stirring time is 10-14 hours. After adding 40-80 μl of the precursor solution, spin coating is performed twice, the speed and time of the first spin coating are: 800-1200 rpm, 8-12 s, and the speed and time of the second spin coating are: 3500-4500 rpm, 25-35 s. The amount of trichlorotoluene added at 4-6 s before the end of the second spin coating is 200-300 μl. The final heat treatment process is 100-140°C for 30-50 minutes.

[0010] Preferably, the size of the film in step (2) is 100-300 μm in side length and 0.01-0.09 mm in area. 2 Polygon (more than 3 sides).

[0011] Preferably, the different pressure range in step (3) is 0 GPa-3 GPa.

[0012] Preferably, in step (4), the certain pressure is 1.5 GPa-2.0 GPa, and the time period is 10 h-24 h. The present invention realizes (FAPbI3) under different pressures 0.95 (MAPbBr3) 0.05 Diffusion coefficient test of polycrystalline thin film. It is found that with the increase of pressure, (FAPbI3) 0.95 (MAPbBr3) 0.05 The diffusion coefficient of the polycrystalline film increases first and then tends to remain constant as the pressure increases. By maintaining the high pressure point for a long time and then releasing the pressure, the high pressure phase (FAPbI3) was successfully 0.95 (MAPbBr3) 0.05The diffusion coefficient of the polycrystalline film is retained to normal pressure. This patent proposes a method for increasing the diffusion coefficient of the perovskite film and capturing its high diffusion coefficient under high pressure to normal pressure.

[0013] Compared with the prior art, the present invention has the following beneficial effects: (1) The perovskite (FAPbI3) synthesized by the method of improving the diffusion coefficient of the perovskite film and capturing the high diffusion coefficient under high pressure to normal pressure of the present invention 0.95 (MAPbBr3) 0.05 Polycrystalline thin films have fewer surface defects. (2) The method of the present invention for increasing the diffusion coefficient of the perovskite film and capturing the high diffusion coefficient under high pressure to normal pressure, thereby obtaining perovskite (FAPbI3) under different pressures 0.95 (MAPbBr3) 0.05 Diffusion coefficient variation in polycrystalline thin films. (3) The method of the present invention for increasing the diffusion coefficient of the perovskite film and capturing its high diffusion coefficient under high pressure to normal pressure successfully converts the high pressure phase (FAPbI3) to a high pressure phase by maintaining the high pressure point for a long time and then releasing the pressure. 0.95 (MAPbBr3) 0.05 The diffusion coefficient of polycrystalline thin films is preserved to ambient pressure. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 (FAPbI3) prepared in Example 1 0.95 (MAPbBr3) 0.05 Polycrystalline thin film diagram. Figure 2 (FAPbI3) prepared in Example 1 0.95 (MAPbBr3) 0.05 Carrier density curves of the fluorescence of polycrystalline films at different pressures after normalization along the x-axis, and the calculation of the diffusion coefficient. Figure 3 (FAPbI3) prepared in Example 1 0.95 (MAPbBr3) 0.05 Diffusion coefficient D of polycrystalline thin films at different pressures. Figure 4 (FAPbI3) prepared in Example 1 0.95 (MAPbBr3) 0.05 The carrier density curve after normalization along the x-axis of the fluorescence at different times of the polycrystalline film under high pressure, as well as the calculation of the diffusion coefficient. Figure 5 (FAPbI3) prepared in Example 1 0.95 (MAPbBr3) 0.05 The diffusion coefficient of polycrystalline thin films maintained at different times under high pressure. DETAILED DESCRIPTION

[0014] The present invention is further described in detail below in conjunction with examples and drawings, but the embodiments of the present invention are not limited thereto. The reagents used in the examples can all be purchased from the market. Measurement of perovskite film fluorescence imaging and calculation of diffusion coefficient: Selecting samples with a side length of 100-300μm and an area of ​​0.01-0.09mm by needle picking 2 Polygon (FAPbI3) 0.95 (MAPbBr3) 0.05 Polycrystalline film (the subscripts 0.95 and 0.05 represent the stoichiometric ratio of the corresponding amount of the substance in the brackets) As for the diamond anvil of the high-pressure press, stainless steel is used as an annular gasket (the inner diameter of the annular gasket is 500μm) and placed on the diamond anvil (diameter 1000μm). A drop of silicone oil is dripped into the gasket. The silicone oil is used as a pressure transmission medium to subject the sample to quasi-hydrostatic pressure. Ruby balls are used for standard pressure; the high-pressure press with the sample is placed on the fluorescence scanning imaging microscope system for carrier diffusion coefficient testing under different pressures. The fluorescence scanning imaging microscope system uses 406nm pulsed light as the excitation light. The excitation light passes through the entrance of the fluorescence scanning imaging system, passes through the 425nm long-pass dichroic mirror (Dichroic Mirrors Long Pass), and then passes through the diamond anvil of the high-pressure press and acts on (FAPbI3) 0.95 (MAPbBr3) 0.05 Polycrystalline thin film sample, excitation light excitation (FAPbI3) 0.95 (MAPbBr3) 0.05 The polycrystalline thin film sample generates fluorescence, which passes through a 425nm long-pass dichroic filter and a 460nm long-pass filter and then enters the detector to collect the fluorescence. The detector (single-photon detector) uses a single-photon counting function, which can achieve time-resolved fluorescence imaging experiments by communicating and synchronizing with the pulsed laser. The calculation process of the diffusion coefficient is as follows (J.Phys.Chem.Lett.11,6956-6963(2020);Nat.Commun.6,7471(2015): (FAPbI3) 0.95 (MAPbBr3) 0.05 The carrier distribution at the initial moment of the polycrystalline film conforms to the Gaussian distribution, so the lateral carrier distribution at any time t can be expressed by the two-dimensional Gaussian distribution equation: Fluorescence intensity distribution I PL (x,y,t) is: I PL(x, y, t) ∝ n(x, y, t) where x0 and y0 are the locations of the excitation points, σ 2 t,x and σ 2 t,y is the Gaussian broadening along the x and y directions that varies with time, and their changes at different delay times represent the transport process of carriers. For diffusion along the x-axis: Where, l = 2(Dt) 1 / 2 , represents the mean square displacement of the carrier from its initial position (along the +x and -x directions) at time t. Therefore, (FAPbI3) 0.95 (MAPbBr3) 0.05 The diffusion coefficient D of the polycrystalline film can be obtained by the following formula: (FAPbI3) 0.95 (MAPbBr3) 0.05 The diffusion coefficient of the polycrystalline film increases first and then tends to remain constant as the pressure increases. By maintaining the high pressure point for a long time and then releasing the pressure, the high pressure phase (FAPbI3) was successfully 0.95 (MAPbBr3) 0.05 The diffusion coefficient of polycrystalline thin films is preserved to ambient pressure.

[0015] Example 1 The method for improving the diffusion coefficient of perovskite film and capturing its high diffusion coefficient under high pressure to normal pressure specifically comprises the following steps: (1) Preparation of perovskite film: accurately weigh methyl ammonium bromide (MABr) (7.84 mg), methyl ammonium chloride (MACl) (26.94 mg), formamidine hydroiodide (FAI) (228.72 mg), lead bromide (PbBr2) (25.69 mg) and lead iodide (PbI2) (613.14 mg) and dissolve them in dimethylformamide (DMF) (800 μl) and dimethyl sulfoxide (DMSO) (200 μl), and stir for 12 hours. 60 μl of the precursor solution is dripped onto a thin glass of 22 mm×22 mm×0.13 mm (length×width×thickness), and then spin-coated twice, the first spin-coating speed and time are: 1000 rpm, 10 s, and the second spin-coating speed and time are: 4000 rpm, 30 s. At 25 seconds after the second spin coating, 250 μl of chlorotoluene was added. The final heat treatment process was 120° C. for 40 minutes. According to the above process (measurement of perovskite film fluorescence imaging and calculation of diffusion coefficient), the perovskite film fluorescence imaging and diffusion coefficient calculation are carried out: the needle picking method is used to select a sample with a side length of 100-300 μm and an area of ​​0.01-0.09 mm. 2 Polygon (FAPbI3) 0.95 (MAPbBr3) 0.05 polycrystalline film (2) Measured at 0.0 GPa (normal pressure), 0.5, 1.3, 1.6, and 2.3 GPa (FAPbI3) 0.95 (MAPbBr3) 0.05 Fluorescence imaging of polycrystalline thin films. (3) Calculate the FAPbI3 at 0.0 GPa (normal pressure), 0.5, 1.3, 1.6, and 2.3 GPa respectively 0.95 (MAPbBr3) 0.05 Diffusion coefficient D of polycrystalline thin film. (4) The FAPbI3 values ​​were measured at 0.0 GPa (normal pressure), pressurized to 1.8 GPa, maintained at 1.8 GPa for 5 h, maintained at 1.8 GPa for 8 h, maintained at 1.8 GPa for 12 h, and then released to normal pressure at 2 h, 7 h, 12 h, 19 h, 24 h, and 26 h after the pressure was released. 0.95 (MAPbBr3) 0.05 Fluorescence imaging of polycrystalline thin films. (5) Calculate the (FAPbI3) at 0.0 GPa (normal pressure), pressurized to 1.8 GPa, maintained at 1.8 GPa for 5 h, maintained at 1.8 GPa for 8 h, maintained at 1.8 GPa for 12 h, and then released to normal pressure after 12 h at 2 h, 7 h, 12 h, 19 h, 24 h, and 26 h. 0.95 (MAPbBr3) 0.05 Diffusion coefficient of polycrystalline thin films.

[0016] (FAPbI3) prepared in this example 0.95 (MAPbBr3) 0.05 Polycrystalline thin films such as Figure 1 As shown. Prepared (FAPbI3) 0.95 (MAPbBr3) 0.05 The polycrystalline film has regular morphology and few surface defects.

[0017] (FAPbI3) prepared in this example 0.95 (MAPbBr3) 0.05The carrier density curve of the fluorescence of the polycrystalline film at different pressures after normalization along the x-axis, and the calculation of the diffusion coefficient are as follows: Figure 2 It can be clearly seen that the broadening of the carrier density curve under high pressure is more obvious than that under normal pressure, which indicates that under high pressure (FAPbI3) 0.95 (MAPbBr3) 0.05 The diffusion coefficient of polycrystalline thin films is larger than that at normal pressure.

[0018] (FAPbI3) prepared in Example 1 0.95 (MAPbBr3) 0.05 Diffusion coefficient test of polycrystalline film under different pressures Figure 3 As shown. It is found that with the increase of pressure, (FAPbI3) 0.95 (MAPbBr3) 0.05 The diffusion coefficient of polycrystalline thin films increases first and then tends to be constant with the increase of pressure.

[0019] (FAPbI3) prepared in Example 1 0.95 (MAPbBr3) 0.05 The carrier density curve of the polycrystalline film maintained at different times under high pressure and normalized along the x-axis, as well as the calculation of the diffusion coefficient are shown in the figure below: Figure 4 As shown. After the high pressure is maintained for a long time and then the pressure is released, the carrier density curve of the film is larger than that of the normal pressure, which is equivalent to the widening of the carrier density curve under high pressure. By maintaining the high pressure point for a long time and then releasing the pressure, the high pressure phase (FAPbI3) is successfully 0.95 (MAPbBr3) 0.05 The diffusion coefficient of polycrystalline thin films is preserved to ambient pressure.

[0020] (FAPbI3) prepared in Example 1 0.95 (MAPbBr3) 0.05 The diffusion coefficient of the polycrystalline film maintained at different times under high pressure is as follows Figure 5 As shown. It is found that the diffusion coefficient under high pressure is greater than that under normal pressure, and the diffusion coefficient after long-term maintenance under high pressure is the same as the diffusion coefficient under high pressure. Therefore, by maintaining the high pressure point for a long time and then releasing the pressure, the high pressure phase (FAPbI3) is successfully 0.95 (MAPbBr3) 0.05 The diffusion coefficient of polycrystalline thin films is preserved to ambient pressure.

[0021] The above examples are preferred implementation schemes of the present invention, but the implementation schemes of the present invention are not specifically limited by the above examples. Any other changes, modifications, simplifications, combinations, substitutions, etc. made without departing from the spirit and principles of the present invention are within the protection scope of the present invention.

Claims

1. A method for improving the diffusion coefficient of a perovskite film, characterized in that: The perovskite film is pressurized to a pressure greater than normal pressure, that is, greater than 0 GPa, preferably greater than 0 GPa to 3.0 GPa.

2. The method according to claim 1, characterized in that: The perovskite film is pressurized to greater than 0 GPa to 3.0 GPa. As the pressure increases, the diffusion coefficient of the perovskite film first increases and then tends to be constant.

3. The method according to claim 1, characterized in that: The perovskite film is pressurized to a pressure greater than normal pressure, that is, greater than 0 GPa to 2.3 GPa, preferably greater than 0 GPa to 2.0 GPa, and most preferably greater than 0 GPa to 1.8 GPa.

4. The method according to claim 1, 2 or 3, characterized in that: The perovskite film is (FAPbI3) 0.95 (MAPbBr3) 0.05 Polycrystalline film.

5. The method according to claim 1, 2, 3 or 4, characterized in that: The specific process is: smash the perovskite film attached to the glass substrate, and then select the area of ​​0.01-0.09mm 2 The polygonal perovskite film is placed on the diamond anvil of a high-pressure press, silicone oil is used as the pressure transmission medium, and an annular gasket with an inner diameter of 400-800μm is used to pressurize the perovskite film to the required pressure.

6. A method for capturing the high diffusion coefficient of a perovskite film under high pressure to normal pressure, characterized in that: The perovskite film is pressurized to 1.0 GPa-2.3 GPa, maintained for 5 h-36 h, and then released to normal pressure.

7. The method according to claim 6, characterized in that: The perovskite film is pressurized to 1.5 GPa-2.0 GPa and maintained for 10 h-24 h; then the pressure is released to normal pressure.

8. The method according to claim 6 or 7, characterized in that: The perovskite film is (FAPbI3) 0.95 (MAPbBr3) 0.05 Polycrystalline film.

9. The method according to claim 6, 7 or 8, characterized in that: The specific process is: smash the perovskite film attached to the glass substrate, and then select the area of ​​0.01-0.09mm 2 The polygonal perovskite film is placed on the diamond anvil of a high-pressure press. Silicone oil is used as the pressure transmission medium and an annular gasket with an inner diameter of 400-800μm is used to pressurize the perovskite film to a certain pressure. After maintaining the high pressure point for a long time, the pressure is released to normal pressure.

Citation Information

Patent Citations

  • Method for preparing inorganic perovskite single crystal thin film through pressure-driven ion diffusion growth

    CN110484963A

  • Method for realizing white light emission by regulating exciton recombination pathway in perovskite

    CN116144342A